New species of Eimeria and Isospora (Protozoa: Eimeriidae) in Geochelone spp. (Chelonia: Testudinidae) from Amazonian Brazil - Lainson R.; Da Silva F.M.M.; Franco C.M.; De Souza M.C. (Parasite, 2008)
Tetrasporocystic, dizoic oocysts of reptiles have been separated by some authors into the genera Eimeria, Choleoeimeria and Acroeimeria (Protozoa: Eimeriidae), based on the site and mode of development of their endogenous stages. The majority of Eimeria species have been, and still are, however, described on oocyst morphology alone. Four different oocysts with this basic morphology were encountered in the faeces of Brazilian tortoises, Geochelone carbonaria Spix, 1824 and are assigned to the genus Eimeria, with the view that they can readily be transferred to the genus Choleoeimeria or Acroeimeria if this is indicated by a future examination of their endogenous development. A morphological comparison distinguishes the oocysts from those of Eimeria spp., previously described in chelonids of the family Testudinidae, and the names E. amazonensis, E. carbonaria, E. carajasensis and E. wellcomei n. spp. are proposed. Coccidial infection appears to be common in G. carbonaria, with three of seven animals examined passing oocysts. Oocysts of Isospora rodriguesae n. sp. (Protozoa: Eimeriidae) are described in the faeces of Geochelone denticulata Linnaeus, 1766. They are morphologically very different from those of Isospora testudae, Davronov, 1985 in Testudo horsfieldi. Eimeria motelo H°urková et al., 2000, previously described in Geochelone denticulata from Peru, is here recorded in the same chelonid from Amazonian Brazil.